Using ‘english teaching courseware package’ in classroom learning: teachers’ perceptions / Suhaibah Ibrahim - Ibrahim, Suhaibah (2011)
The purpose of the study is to explore the utilisation of the English Teaching Courseware Package in school, specifically on the influence of its frequent use to students, the impacts of its content and the challenges that teachers encounter in the implementation in classroom learning. The study is mainly based on teachers' perceptions. The samples of the study are both primary and secondary English teachers in Terengganu. The findings indicate that the frequent use of the courseware does improve students' interests in learning language but the content does not massively play its role in improving students' language skills. It is also found the most dominant challenges to teachers in implementing the courseware in teaching are time factor, technical support and the content of the courseware itself which neglects the seven basic teaching principles. These shortcomings are the factors that prevent teachers to make full use of the courseware in classroom teaching. It is recommended that the Ministry of Education make some revisions on the courseware design so that the investment in such technology would not be a waste.